Differential analyses of peripheral blood parameters in CCR5 inhibition-treated colorectal cancer patients reveal dynamic changes linked to clinical outcomes - Ahmed, Azaz; Halama, Niels (Anticancer research, 2020)
Background/Aim: Chemokine receptor inhibition is an immunotherapy that modulates the innate arm of the immune system. Previous work in microsatellite-stable metastatic colorectal cancer showed an exploitive loop that could be successfully targeted via C-C-motive-chemokine-receptor 5 (CCR5) specific blocking, resulting in a selective anti-tumoral activation of macrophages. In the respective trial (MARACON trial, NCT01736813) the peripheral blood laboratory markers and cytokine values were measured over time. Little is known on their role as biomarkers or stratification parameters in immunotherapy trials. Patients and Methods: Systematic analyses of key laboratory parameters are presented, highlighting specific dynamics of lymphocyte and monocyte percentages, lactate dehydrogenase as well as interleukin-6 and interleukin-8 levels as parameters of a systemic inflammatory readout. Results: Specific dynamical changes of lymphocyte and monocyte compositions were noted between different patients, showing a stabilization (or increase) versus decreased numbers over time for monocytes. While lactate dehydrogenase, interleukin-6 and interleukin-8 showed almost uniformly rising levels over time, the systemic monocyte patterns prompted a further evaluation. Stabilized or increasing monocyte percentages were associated with improved overall survival (Kaplan Meier analysis, p=0.025) and with induced overt radiologic necrosis in patients. Conclusion: The observed association between monocyte dynamics and imaging findings as well as overall survival suggests that analyses of dynamical parameters in the peripheral blood should be implemented in immunotherapy trials.